The Notorious Harmful Algal Blooms-Forming Dinoflagellate Prorocentrum donghaiense Produces Sexual Resting Cysts, Which Widely Distribute Along the Coastal Marine Sediment of China - Hu, Zhangxi; Liu, Yuyang; Deng, Yunyan; Tang, Ying Zhong (Frontiers in Marine Science, 2022)
The armored dinoflagellate Prorocentrum donghaiense distributes globally and has been forming large scale and dense ecosystem disruptive algal blooms in the East China Sea (ECS) almost every year since the 1990s and often in other coastal waters of the world. It has long been a mystery, however, about how these blooms were seeded or where the initiating population came from. While Taiwan Warm Current was recently proposed to seed annual blooms in the ECS, this mechanism, however, cannot be applied to those blooms occurred in other regions such as the coast of Mexican Pacific, Mediterranean Sea, etc. Here, based on laboratory observation on the life cycle transition in clonal cultures and morpho-molecular detections in field sediment samples collected along the coast of China, we provide a more feasible and universal seeding mechanism, formation of resting cysts. Using light microscopy, we confirmed sexual reproduction according to the observations of mating cells in pairs, planozygotes having two similar flagella, darkened and thick-walled resting cysts with smooth surface, and germination processes of resting cyst. Using morpho-molecular detection, we confirmed resting cyst production of P. donghaiense in the field, including the positive detections of PCR using species-specific primers and then the fluorescence in situ hybridization (FISH) using species-specific probes, and further confirmation via single-cell PCR amplification, cloning, and sequencing for the individual FISH-detected cysts. Furthermore, the distribution and abundance of P. donghaiense cysts along the coast of China Seas were mapped using an approach combining real-time PCR (qPCR) and FISH. Resting cysts of this species were found to widely distribute in YS, ECS, and SCS, with a relatively low abundance at most sampling sites , but to be absent in the eight samples from the BS. Resting cyst production confirmed with evidences from both laboratory cultures and field sediments and the extensive distribution of cysts in the China Seas, as the first case in planktonic species of Prorocentrum, not only filled up a knowledge gap about the life history of P. donghaiense but also provided a possible mechanistic facility to seed the annual blooms in the ECS and the global distribution of the species.